Prosthodontic Management of Flabby Ridge with Modified Impression Technique: A Case Report - Maskey, B; Kandel, K; Regmi, M (Journal of Nepalese Prosthodontic Society, 2024)
Complete denture is a commonly used prosthesis used to replace missing dentition and associated structures in oral cavity. The success of complete denture is dependent on several factors, among which the health of the underlying denture bearing area plays a significant role. Any compromises on the quality of these denture resting areas, be it in the form of inflammation, ulceration, hyperplastic tissue, to name a few, will certainly affect the overall prognosis of the dentures. Compromised quality in the form of flabby ridge is not an uncommon clinical presentation and should always be considered during denture fabrication. Attempts have been made, both surgically and conservatively to accommodate these tissues. This case report describes one of the conservative methods wherein modification in impression making using conventional impression material was undertaken.